Základní prvky odhalování, prověřování a vyšetřování trestného činu poškozování lesa podle § 295 trestního zákoníku z pohledu znalce - Cach, Adam (Vysoké učení technické v Brně, Ústav soudního inženýrství, 2014)
Crimes which are commited against the environment, mainly against forest stands, are still actual and, in dead, in last decades with increasing tendency. It is appropriate that a forensic expert the field of study, which authorities active in criminal proceedings entered report, was familiar with the basic procedures that make the police in detecting, examining and investigating crimes forest damage according to § 295 of the Criminal Code. Criminal files submitted must contain the relevant facts which form the basis for preparing an expert report.

Trestná činnost páchaná na životním prostředí, zvláště pak na lesních porostech, je stále aktuální problematikou, která má v posledních letech vzrůstající tendenci. Je vhodné, aby soudní znalec příslušného oboru, jemuž orgány činné v trestním řízení zadávají posudky, byl seznámen se základními postupy, které činí policie při odhalování, prověřování a vyšetřování trestných činů poškození lesa dle § 295 trestního zákoníku. Předložené trestní spisy musí obsahovat relevantní skutečnosti, které tvoří podklad pro zpracování znaleckého posudku.
Basic elements of detection, examination and investigation of the crime related to forest disturbances with respect to § 295 of the criminal code from the perspective of an expert
Keywords: forest disturbance; crime; investigation; evidence; forensic expert; poškození lesa; trestný čin; odhalování zločinu; dokumentace; soudní znalectví